Protective effects of melatonin against carbon tetrachloride-induced hepatotoxicity in rats: a light microscopic and biochemical study - Kus, I; Ogeturk, M; Oner, H; Sahin, S; Yekeler, H; Sarsilmaz, M (Wiley, 2005)
The aim of this study was to examine the protective effects of melatonin against CCl4-induced hepatotoxicity in the rat. Twenty-four male Wistar rats were divided into three groups. Group I was used as a control. Rats in group 11 were injected every other day With CCl4 for 1 month, whereas rats in group III were injected every other day with CCl4 and melatonin for I month. At the end of the experiment, all animals were killed by decapitation and blood samples were obtained. Serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), total and conjugated bilirubin levels were determined. For histopathological evaluation, livers of all rats were removed and processed for light microscopy. All serum biochemical parameters were significantly higher in animals treated with CCl4 than in the controls. When rats injected with CCl4 were treated with melatonin, significantly reduced elevations in serum biochemical parameters were found. In liver sections of the CCl4-injected group, necrosis, fibrosis, mononuclear cell infiltration, haemorrhage, fatty degeneration and formation of regenerative nodules were observed. Additionally, apoptotic figures, microvesicular steatosis and hydropic degeneration in hepatocytes were seen in this group. In contrast, the histopathological changes observed after administration Of CCl4 were lost from rats treated with CCl4 and melatonin. Except for mild hydropic degeneration of the hepatocytes, a normal lobular appearance was seen in the livers of this group. The results of our study indicate that melatonin treatment prevents CCl4-induced liver damage in rats. Copyright (c) 2004 John Wiley & Sons, Ltd.
Keywords: carbon tetrachloride; hepatotoxicity; melatonin; rat; light microscopy